Innovative aspects of modern strategic management of agro-industrial enterprises - O. A. Boris; V. N. Parakhina; K. M. Baryshnikov (Вестник Северо-Кавказского федерального университета, 2025)
Introduction. Global economic crises and geopolitical problems of our time are the most serious challenges for all economic entities of our country, the solution of which is possible only through scientifically based, deep analysis of the situation and the development of strategically correct decisions.Goal. The study determines innovative directions of development of enterprises of the agro-industrial complex based on the application of strategic management methods.Materials and methods. The study is based on a logical critical analysis of literary sources on the research issues, a strategic analysis of the activities of the agro-industrial complex enterprise to determine innovative development paths, synthesis of results, induction and deduction – to integrate conclusions from the results of theoretical and practical research on the application of strategic management.Results and discussion. The main characteristics of the external and internal conditions in which the subjects of economic relations of the agro-industrial complex carry out their activities were identified, the main of which is the property of rapid and unpredictable changes over time. This fact determines the urgent need to develop the ability of agro-industrial complex enterprises to adapt to changing conditions and the use of strategic methods and models suitable for this moment.Conclusion. Based on the results of the study, it can be concluded that all enterprises in our country need to engage in strategic management at a high professional level, and those who have experience in developing and implementing strategies, urgently update them taking into account new conditions and the need to determine the paths of innovative development.